2021
DOI: 10.3390/biology10040336
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Determinants of Obesity, Insulin Resistance and Metabolic Health

Abstract: Obesity caused by the overconsumption of calories has increased to epidemic proportions. Insulin resistance is often associated with an increased adiposity and is a precipitating factor in the development of cardiovascular disease, type 2 diabetes, and altered metabolic health. Of the various factors contributing to metabolic impairments, nutrition is the major modifiable factor that can be targeted to counter the rising prevalence of obesity and metabolic diseases. However, the macronutrient composition of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 238 publications
(235 reference statements)
2
16
0
3
Order By: Relevance
“…However, our result is similar to the Kerala DPP study, which also found that the effect on HbA1c was stronger than on weight [16]. One explanation is that HbA1c changes may be related to dietary changes or changes in physical activity independent of weight loss [43,44].…”
Section: Plos Medicinesupporting
confidence: 87%
“…However, our result is similar to the Kerala DPP study, which also found that the effect on HbA1c was stronger than on weight [16]. One explanation is that HbA1c changes may be related to dietary changes or changes in physical activity independent of weight loss [43,44].…”
Section: Plos Medicinesupporting
confidence: 87%
“…Several prospective investigations have studied the relationship between the dietary glycemic index and the development of type II diabetes, a common consequence of insulin resistance [ 40 ]. Specifically, Villegas et al studied a cohort of over 64,000 Chinese women with no history of diabetes or other chronic disease for almost five years [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by‐different prospective studies, waist/height ratio rather than BMI and WHR is an accurate index for predicting dyslipidemia, hypertension, and MetS 48,49 . Despite several simple methods available to assess abdominal adiposity, proactive management of this disorder at an early stage is of serious concern 50–52 . It has been shown from epidemiological and experimental studies that physical activity/exercise could induce mobilization of visceral fat and reduce central adiposity 53 .…”
Section: Pathophysiology Of Metsmentioning
confidence: 99%